L’argumentation et les descriptions définies - Kohei Kida (Discours)
Utterances in which a referentially used definite description occurs as subject term may sometimes receive an argumentative interpretation, according to which the subject serves to introduce and justify the predicate. This paper aims to give an account of this “argumentative” use of definite descriptions within the framework of an argumentation-based semantics, Marion Carel’s “theory of semantic blocks”. Especially, it will be argued that a definite description can be used argumentatively in an utterance when its function is to provide a schema on the basis of which the argumentative interpretation of the utterance is constructed.